Imatinib activity on Schistosoma mansoni. - Katz, Naftale (2013)
Fundação Oswaldo Cruz. Centro de Pesquisas René Rachou. Laboratório de Esquistossomose. Belo Horizonte, MG, Brasil/Academia Mineira de Medicina. Belo Horizonte, MG, Brasil